Stage‐specific direct health care costs in patients with cutaneous malignant melanoma. (23rd March 2015) - Lyth, J.; Carstensen, J.; Synnerstad, I.; Lindholm, C.
Abstract: Background: Clinical stage at diagnosis is a strong prognostic factor for death in cutaneous malignant melanoma (CMM), with worse prognosis at higher stages. However, few studies have investigated how direct health care cost per patient varies with clinical stage. Objective: The aim of this study was to determine the stage‐specific direct health care costs for CMM patients compared to the health care costs in the general population in the County of Östergötland, Sweden. Methods: Cutaneous malignant melanoma patients in the County of Östergötland diagnosed 2005–2012 were identified from the Swedish cancer registry. Information on clinical stage was collected from the Swedish Melanoma Register (SMR) and cost data from the Cost per Patient database (CPP) for 1075 CMM patients in Östergötland. CPP contains costs associated with all health care contacts per patient including inpatient, outpatient and primary care. The CMM‐related costs were defined as the difference in mean health care costs between CMM patients and general population. Results: The first year after CMM diagnosis, the average health care costs for CMM patients were 2.8 times higher than in the general population. The health care cost ratio varied from 2.0 (stage I) to 10.1 (stage IV) and the CMM‐related costs per patient‐year varied from €2 670 (stage I) to €29 291 (stage IV). The mean health care costs decreased over time but remained significantly higher than in the general population for all clinical stages. During the first year after diagnosis, patients in clinical stage III–IV (7% of CMM patients) accounted for 27% of the total CMM‐related health care costs. Conclusions: The direct health care costs for CMM patients were significantly higher than in the general population independent of clinical stage. CMM patients diagnosed in clinical stage III–IV were associated with particularly high costs and the health care system may save resources by finding CMM patients in earlier stages.